THE INFLUENCE OF ON AND OFF CAMPUS ACCOMMODATIONS ON POST SECONDARY SCHOOLS STUDENTS ACADEMIC PERFORMANCE IN KALTUNGO LOCAL GOVERNMENT AREA, GOMBE STATE - Isa, Peter Gerson; Ikenna, Ihejiofor Kingsley; Ebuka, Oyim Eric (International Journal Multidisciplinary (IJMI), 2026)
Objective: Student housing has a significant impact on academic progress, well-being, and social integration at postsecondary campuses. This study examines the impact of on-campus and off-campus housing on postsecondary school students' academic performance in Kaltungo LGA. Method: A descriptive survey approach was used, including 300 students from both private and government post-secondary schools in the research region. Data were gathered using structured questionnaires and evaluated with descriptive statistics and independent t-tests. Results: The data found considerable disparities in academic performance among lodging types, with on-campus students usually outperforming off-campus students. Access to friends, outdoor social activities, relationships, academic resources, time management, security, and environmental distractions are all important elements in determining this. Novelty:The study suggests that addressing both on-campus and off-campus living circumstances will improve academic achievements.